ANALYSIS OF MOVEMENT RESISTANCE OF CONVEYOR BELT AND ROLLERS IN THE COAL MINE MYSŁOWICE-WESOŁA - Tadeusz OPASIAK; Damian GĄSKA; Bogusław ŁAZARZ (Scientific Journal of Silesian University of Technology. Series Transport)
The paper presents a study of new design of SAG rollers. The study focused on the measurement of static and dynamic resistance of rotating rollers and the impact of new construction on the power consumption of the conveyor. Rollers have been modified through the use of class C4 bearing seals and labyrinth seal U4Exp 62/65 with a cover 2LU4 of runner construction. Measurements of static and dynamic resistance of rotating rollers were made on a universal rollers test bench, and power measurements were carried out on a belt conveyor power supply system Gwarek 1200 No. TW in KWK Mysłowice-Wesoła